Ponyo e “A sereiazinha”: análise das relações dialógicas - Brito, Bruna Perrella (2018)
The purpose of this work is to analyze the dialogism between the animation Ponyo on the Cliff by the Sea and “The Little Mermaid”. We study the mechanisms between the audiovisual text and the verbal one; the historical moment that they were produced; and we show that our cultural repertory make possible to see (or not) the dialogue between the discourses, throwing light over meanings existent, that would not be perceived without the dialogism identification. We study the discourse’s mechanisms used to appropriate the discourse of the other when it change its language and we analyze if it was preserved the narration retaken and what kinds of changes occurred related to the original text when the dialogue occurred between the discourses. To our aim, we use Bakhtin’s propositions about the characteristics that define the concrete statement. With Bakhtin, we considered that the book and the animation are texts and the dialogue between them is possible without the need of using intersemiotics concepts to analyze them. Beth Brait gave us the fundamental to analyze a text as a concrete statement. Therefore, we used the concepts and theories showed by Bakhtin and his Circle of a general theory of the language because they covers other kinds of languages beyond the verbal discourses and written texts. In the work, we put in practical analytically, in a definite corpus, theoretical conceptions of the Circle of Bakhtin.